Histone modifications and depression: epigenetic mechanisms, therapeutic targets, and translational outlook - Lv, Liang-Zhen; Wang, Zhao-Di; Ren, Jia-jie; Li, Lu-Hao; Liu, Xian-bao; Li, Jia-li; Zhu, Hui; Jiang, Bei; Han, Ya-peng; Zhou, Xue-ming; Ren, Li; Chang, Zhuo (Frontiers in Genetics, 2026)
Major depressive disorder (MDD) is a highly prevalent and heterogeneous psychiatric disorder shaped by the interplay of genetic, environmental, and epigenetic factors. Histone modifications, particularly acetylation and methylation, have emerged as critical regulators of chromatin dynamics and gene expression in stress adaptation, neuroplasticity, and emotional regulation. This review synthesizes current evidence linking dysregulated histone deacetylases (HDACs) and histone methyltransferases (HMTs) to impaired neuroplasticity, neuroinflammation, mitochondrial dysfunction, and hypothalamic–pituitary–adrenal (HPA) axis hyperactivity in depression. We further evaluate the therapeutic potential of HDAC and HMT inhibitors, highlight their effects beyond transcriptional control, and discuss peripheral epigenetic biomarkers as candidate tools for patient stratification and treatment prediction. Emerging technologies, including single-cell and spatial epigenomics as well as CRISPR-based epigenetic editing, are outlined as future avenues toward precision medicine. While isoform specificity, off-target effects, and translational heterogeneity remain major challenges, targeting histone modifications represents a promising strategy for next-generation antidepressant development.